A nonlinear component mode synthesis method for the computation of steady-state vibrations in non-conservative systems. (15th January 2017) - Joannin, Colas; Chouvion, Benjamin; Thouverez, Fabrice; Ousty, Jean-Philippe; Mbaye, Moustapha
Abstract: This paper presents an extension to classic component mode synthesis methods to compute the steady-state forced response of nonlinear and dissipative structures. The procedure makes use of the nonlinear complex modes of each substructure, computed by means of a modified harmonic balance method, in order to build a reduced-order model easily solved by standard iterative solvers. The proposed method is applied to a mistuned cyclic structure subjected to dry friction forces, and proves particularly suitable for the study of such systems with high modal density and non-conservative nonlinearities. Abstract : Highlights: A new component mode synthesis method to study nonlinear systems is proposed. The reduced order model makes use of the nonlinear complex modes of the components. The method is tested on a mistuned model of bladed-disk subjected to dry friction. Excellent accuracy and computational performance are achieved.